Biomechanical comparison of different cerclage types in addition to an angle stable plate osteosynthesis of distal tibial fractures. Issue 8 (August 2021) - Förch, Stefan; Sandriesser, Sabrina; Mayr, Edgar; Schrödl, Falk; von Rüden, Christian; Augat, Peter
Abstract: Background: Different stand-alone cerclage configurations and their optimal twisting techniques have been investigated over the years. This study tests for the stabilizing effect of different supplemental cerclage materials in combination with locked plating of distal tibia fractures. Methods: Locking plate fixation of a distal tibial spiral fracture was tested as stand-alone and with supplemental cerclage materials (one cable, two cables, wire, fiber tape). Construct stiffness and fracture gap movements were investigated under quasi-static and dynamic loads and compared to the stand-alone locking plate. Results: With each of the tested cerclages, stiffness was significantly higher than for a solitary plate osteosynthesis. Most reduction in fracture gap movement was achieved by cable cerclages, followed by double-looped wire and double-looped fiber tape cerclages. Under dynamic loading an additional cable cerclage reduces excessive gap movement. Conclusion: Compared to solitary plate osteosynthesis all supplemental cerclage materials were generally superior with reduced fracture gap movements whereas cable cerclages showing the greatest stabilizing effect.